Alpha-Fetoprotein Slope >7.5 ng/mL per Month Predicts Microvascular Invasion and Tumor Recurrence After Liver Transplantation for Hepatocellular Carcinoma. Issue 5 (May 2018) - Giard, Jeanne-Marie; Mehta, Neil; Dodge, Jennifer L.; Roberts, John P.; Yao, Francis Y.
Abstract : Background: Rising alpha-fetoprotein (AFP) is a potential marker of worse prognosis after liver transplant (LT) for hepatocellular carcinoma (HCC), but prior studies relied on only 2 data points and were imprecise in assessing AFP slope. The aim of this study was to examine the association between AFP slope and post-LT HCC recurrence, with AFP slope estimated from multiple data points over time. Methods: Our cohort included 336 patients undergoing LT with Model for End Stage Liver Disease exception for HCC within Milan criteria from 2003 to 2013. Most (98%) had pre-LT locoregional therapy. AFP slope was estimated by fitting a regression line to the AFP levels over time. Results: The 1- and 5-year post-LT survivals were 94% and 77% and 1- and 5-year recurrence-free probabilities were 95% and 86%, respectively. In univariate analysis, HCC recurrence was significantly associated with microvascular invasion (hazard ratio [HR], 13.1; P <0.001), tumor grade (HR, 1.8; P <0.001), pathologic stage >Milan criteria (HR, 8.9; P <0.001), 3 tumor nodules (HR, 5.5; P =0.002), AFP slope greater than 7.5 ng/mL per month (HR, 3.9; P =0.005), and female sex (HR, 2.3; P =0.01). In multivariable analysis of factors known before LT, 3 tumor nodules (HR, 7.6; P <0.001), female sex (HR, 2.5; P =0.01), and AFP slope >7.5 (HR, 3.0; P =0.03) were significantly associated with HCC recurrence. AFP slope greater than 7.5 was also associated with microvascular invasion (odds ratio, 6.8; P =0.008). Conclusions: AFP slope increasing greater than 7.5 ng/mL per month despite locoregional therapy is associated with post-LT HCC recurrence and may serve as a surrogate for microvascular invasion. These findings support incorporating changes in the AFP into candidate selection for LT. Abstract : Optimizing the prediction of HCC recurrence, and therefore the allocation of organs to ensure the best outcomes, remains a work in progress. The authors demonstrate the use of AFP as a dynamic marker for improved prediction of biologic risk to complement the morphologic criteria in HCC candidate selection.